2010
DOI: 10.1016/j.ijsolstr.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of self-consistent polycrystal plasticity models for magnesium alloy AZ31B sheet

Abstract: a b s t r a c tVarious self-consistent polycrystal plasticity models for hexagonal close packed (HCP) polycrystals are evaluated by studying the deformation behavior of magnesium alloy AZ31B sheet under different uniaxial strain paths. In all employed polycrystal plasticity models both slip and twinning contribute to plastic deformation. The material parameters for the various models are fitted to experimental uniaxial tension and compression along the rolling direction (RD) and then used to predict uniaxial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(135 citation statements)
references
References 49 publications
11
117
1
Order By: Relevance
“…A deformation texture, in which basal planes are parallel to the rolling plane and (10-10) directions are parallel to the loading axis (RD), becomes progressively better defined with increasing deformation. This reveals that the main deformation mechanism is prismatic slip, together with basal slip [4,5,40,41]. At the largest strain level investigated (0.20, Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…A deformation texture, in which basal planes are parallel to the rolling plane and (10-10) directions are parallel to the loading axis (RD), becomes progressively better defined with increasing deformation. This reveals that the main deformation mechanism is prismatic slip, together with basal slip [4,5,40,41]. At the largest strain level investigated (0.20, Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Accordingly, the grain size increases to 12|jim, as twin propagation has now basically encompassed the entire grains and very few twin boundaries remain. It is well known that the twinned regions, in which the compression axis is parallel to the c-axes, pyramidal (c + a) and basal slip are the predominant deformation mechanisms [39,40]. As shown in Figs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The code used in the present work is that developed at Los Alamos by Lebensohn and Tome´[ 17,18] and has been proven for the simulation of magnesium deformation including slip and twinning. [19,20] Note that the VPSC model considers only homogeneous deformation, and does not account for strain localization effects (e.g., shear banding).…”
Section: Deformation Simulationsmentioning
confidence: 99%
“…[26] have demonstrated that the predicted response of a polycrystal is very sensitive to the self-consistent scheme employed. Wang et al [30] have evaluated various self-consistent schemes used in selfconsistent modeling by applying them to the large strain behavior of magnesium alloy AZ31B plate under different deformation processes. It was found that the Affine self-consistent scheme gave the best overall performance among the self-consistent approaches examined.…”
Section: Constitutive Modelmentioning
confidence: 99%